A psychology of the human brain–gut–microbiome axis. Issue 4 (April 2017) - Allen, Andrew P.; Dinan, Timothy G.; Clarke, Gerard; Cryan, John F.
Abstract: In recent years, we have seen increasing research within neuroscience and biopsychology on the interactions between the brain, the gastrointestinal tract, the bacteria within the gastrointestinal tract, and the bidirectional relationship between these systems: the brain–gut–microbiome axis. Although research has demonstrated that the gut microbiota can impact upon cognition and a variety of stress‐related behaviours, including those relevant to anxiety and depression, we still do not know how this occurs. A deeper understanding of how psychological development as well as social and cultural factors impact upon the brain–gut–microbiome axis will contextualise the role of the axis in humans and inform psychological interventions that improve health within the brain–gut–microbiome axis. Interventions ostensibly aimed at ameliorating disorders in one part of the brain–gut–microbiome axis (e.g., psychotherapy for depression) may nonetheless impact upon other parts of the axis (e.g., microbiome composition and function), and functional gastrointestinal disorders such as irritable bowel syndrome represent a disorder of the axis, rather than an isolated problem either of psychology or of gastrointestinal function. The discipline of psychology needs to be cognisant of these interactions and can help to inform the future research agenda in this emerging field of research. In this review, we outline the role psychology has to play in understanding the brain–gut–microbiome axis, with a focus on human psychology and the use of research in laboratory animals to model human psychology.